Emergency department utilisation for inflammatory bowel disease in the United States from 2006 to 2014. Issue 7 (7th February 2018) - Ballou, S.; Hirsch, W.; Singh, P.; Rangan, V.; Nee, J.; Iturrino, J.; Sommers, T.; Zubiago, J.; Sengupta, N.; Bollom, A.; Jones, M.; Moss, A. C.; et al.
Summary: Background: Despite advances in treatment, patients with inflammatory bowel disease (IBD) frequently require emergency department (ED) visits and hospitalisations. Aims: To analyse trends in ED visits and subsequent hospitalisations for IBD in the United States (US). Methods: Data were analysed from the Nationwide Emergency Department Sample (NEDS) years 2006‐2014. The NEDS is the largest all‐payer ED database in the US, weighted to represent 135 million visits/year. IBD was identified using ICD‐9 codes for Crohn's disease (CD) or ulcerative colitis (UC). Surgeries were identified using procedure codes. Results: The frequency of IBD‐ED visits increased 51.8%, from 90 846 visits in 2006 to 137 946 in 2014, which was statistically significant in linear regression. For comparison, all‐case ED use between 2006 and 2014 increased 14.8%. In‐patient hospitalisations from the ED decreased 12.1% for IBD (from 64.7% rate of hospitalisation from the ED in 2006 to 52.6% in 2014), with a UC:CD ratio of 1.2:1 in 2006 and 1.3:1 in 2014. Chi‐square analysis revealed that this was a significant decrease. Surgery rates also showed a statistically significant decrease. The mean ED charge per patient rose 102.5% and the aggregate national cost of IBD‐ED visits increased 207.5%. CD accounted for over twice as many visits as UC in both years. UC, age, male gender, highest income quartile, private insurance, Medicaid/Medicare, and tobacco use were associated with in‐patient admissions. Conclusions: The number of ED visits due to IBD and associated charges have continued to rise, while the rates of in‐patient hospitalisations referred from the ED and surgeries have decreased. Abstract : Linked Content This article is linked to Mak and Ng paper. To view this article visithttps://doi.org/10.1111/apt.14601 .